Paróquias metropolitanas: entre os sujeitos e seus hibridismos - Marchini, Welder Lancieri (Revista eclesiástica brasileira, 2019)
The process of metropolitan construction has a significant impact on the religious experience of its inhabitants. Starting from this affirmation, this article has as object the intersection between the metropolitan context and the parochial religious experience. For this the research interprets the conditions of the metropolitan individual, namely, his individuality, relation with the institutions and his moral, describes the history and the transformations of the parochial structures. We consider that religion in a metropolis context can only be understood in the perspective of a hybrid society. As a response to the variety of metropolitan individuals, religion assumes the characteristic of providing service, seeking to serve the most varied public, which hybridize in the parish environment.